On Strong Complete Monomials and Its Multiplicative Analogue Over Finite Fields - Muratović-Ribić, Amela; Surdulli, Shaip (Sarajevo Journal of Mathematics, 2022)
We present an extended class of complete and strong complete monomials over a finite field. These monomials can also be viewed as generalized complete and strong complete mappings. In the second part of the article we give basic properties of polynomials induced by complete mappings, orthomorpisms and strong complete mappings over a multiplicative group of the finite field.